Self-powered graphene/black-ge photodetectors enhanced by simultaneous nanotexturing and self-passivation - Park, Hyunjung (2024)
Black germanium (Ge) exhibits exceptional light absorption, holding significant promise for optoelectronic applications. However, achieving self-powered photodetection performance in black Ge is challenging due to its high surface recombination rate. Herein, this challenge is addressed by demonstrating self-powered Graphene (Gr)/black-Ge Schottky photodiodes, achieved through simultaneous nanotexturing and high-quality self-passivation. This approach involves utilizing reactive ion etching with Cl2 and BCl3 to achieve Cl-passivated black Ge. Optical analysis reveals excellent optical characteristics in both Cl2-treated and BCl3-treated samples, including a high aspect ratio of 1.9 and a low reflectance of 1.5%. Notably, the Cl2-treated black Ge exhibits a higher carrier lifetime of 20.4 µs compared to the 11.7 µs lifetime of the BCl3-treated black Ge, attributed to the self-passivation induced by Cl2 plasma, effectively mitigating defects. Surface composition analysis further confirms the substantial role of Cl in passivation. Significantly, these improved properties translate into notable advancements in device performance, including an enhancement in responsivity from 21 to 276 mA W−1 when compared to planar Gr/Ge devices. These findings underscore the potential of Cl2 RIE for developing high-performance Ge-based optoelectronic devices.